Comparison of the aggregate production plan under methodologies of American and European authors - Chaves-Aguilar, Felipe (2020)
The objective of the study was to compare the cost of the aggregate polyethylene terephthalate (PET) bottle manufacturing plan calculated by American and European methodologies for six scenarios of the aggregate process plan, whose difference lies in the modification of its decision variables. Demand forecasts were estimated using the Winters method, the results of the aggregate plans in the application of the case study were based on the application of the inverse transform method for a uniform distribution. It is observed that the cost of production of the aggregate plan by methodologies of European authors is greater because it considers more variables such as labor and backlogs that the American approach does not add up. Normally you cannot make a decision if there are more or fewer variables of cost since it is the forecasts that dictate the course.